2011
DOI: 10.1016/s1734-1140(11)70708-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel I1-imidazoline S43126 enhance insulin action in PC12 cells

Abstract: Abstract:The I 1 -imidazoline receptor is a novel target for drug development for hypertension and insulin resistance, major disorders associated with type 2 diabetes. In the present study, we examined the effects of a novel imidazoline agonist S43126, on phosphorylation of protein kinase B (PKB/Akt) and extracellular signal-regulated kinase (ERK1/2) in PC12 cells. We further examined the effects of S43126 on insulin stimulated PKB and ERK phosphorylation. PC12 cells were treated with varying doses of S43126 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Recent work revealed that ligand activation of the imidazoline receptor (I1R) enhances insulin action in PC12 cells. 23 The novel I1R agonist S43126 (2-[4′-methoxyphenyl]-4,5-dihydro-1 H -imidazole) and the known antihypertensive and I1R agonist moxonidine are both capable of engaging this phenomenon. Moreover, moxonidine normalizes plasma insulin levels in an animal model and improves glucose uptake in peripheral cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work revealed that ligand activation of the imidazoline receptor (I1R) enhances insulin action in PC12 cells. 23 The novel I1R agonist S43126 (2-[4′-methoxyphenyl]-4,5-dihydro-1 H -imidazole) and the known antihypertensive and I1R agonist moxonidine are both capable of engaging this phenomenon. Moreover, moxonidine normalizes plasma insulin levels in an animal model and improves glucose uptake in peripheral cells.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, S43126 is a novel compound that activated I 1 -imidazoline receptors but not α-adrenoceptors [ 23 , 38 ]. We have shown that S43126 induced insulin secretion in a dose and time dependent manner.…”
Section: Discussionmentioning
confidence: 99%